Development of a mathematical model and selection of optimal parameters for neutralizing wastewater via the electrohydraulic effect (The Peerian Journal, 2026)
This study explores the application of the electrohydraulic effect as an alternative method for disinfecting wastewater. It details the construction of a laboratory-scale setup and outlines the interchangeable components involved in the treatment proces s. A mathematical model has been developed to simulate the electrohydraulic treatment, accompanied by an optimization study of key parameters such as discharge voltage, capacitor capacity, and treatment duration. These variables were analyzed through statistical experimental design methods. A second-order regression model was formulated to predict disinfection efficiency, and its validity was confirmed using Student’s t-test and Fisher’s F-test. Optimal operating conditions were established, achieving high treatment efficiency while maintaining ecofriendliness and energy conservation. In addition to conventional disinfection methods, this work emphasizes the importance of innovative technologies in modern wastewater treatment research